2022
DOI: 10.2166/wcc.2022.211
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of breaking wave impact loads on a vertical seawall retrofitted with different geometrical configurations of recurve parapets

Abstract: Experiments are the traditional techniques used in coastal engineering to study complex wave structure interactions. However, with the advent of high-performance computing, even performing 1:1 scale numerical simulations has become a reality. The progress aids in extending the parametric investigation or repeating the procedure for comparable structures. In this study, a numerical model in OpenFOAM® with waves2Foam wave boundary conditions is used to simulate wave structure interactions at seawalls with varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Physically modelled data is generally used in further analysis and can underpin a sensitivity analysis to determine the influential overtopping parameters (see for example, [4][5][6][7]). With the advancement of computational fluid dynamics techniques, numerical models have been adopted to investigate wave overtopping and wave impact loads at sea defences (see for example, [8][9][10][11] presented a tool for predicting the magnitude of infragravity waves, which are long-period ocean waves in coastal areas with shallow foreshores and dikes. The tool is based on numerical models and considers factors such as wave height, water depth, and foreshore slope to make predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Physically modelled data is generally used in further analysis and can underpin a sensitivity analysis to determine the influential overtopping parameters (see for example, [4][5][6][7]). With the advancement of computational fluid dynamics techniques, numerical models have been adopted to investigate wave overtopping and wave impact loads at sea defences (see for example, [8][9][10][11] presented a tool for predicting the magnitude of infragravity waves, which are long-period ocean waves in coastal areas with shallow foreshores and dikes. The tool is based on numerical models and considers factors such as wave height, water depth, and foreshore slope to make predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Cooker and Peregrine call this effect flip-through. Ravindar et al found that when a seaward curved parapet is installed at the top of the wall, flip-through leads to a deflected water jet and large forces on the top part of the wall [20].…”
Section: Introductionmentioning
confidence: 99%